Balloon Dilatation of Pediatric Subglottic Laryngeal Stenosis during the Artificial Apneic Pause: Experience in 5 Children. (12th June 2014) - Lisý, J.; Groh, D.; Chovanec, M.; Marková, M.; Suchánek, V.; Polášková, P.; Trávníček, M.
Abstract : Introduction . Balloon dilatation is a method of choice for treatment of laryngeal stenosis in children. The aim of procedure in apneic pause is to avoid new insertion of tracheostomy cannula. Patients and Methods . The authors performed balloon dilatation of subglottic laryngeal strictures (SGS) in 5 children (3 girls and 2 boys) without tracheotomy. Two of them with traumatic and inflammatory SGS had a tracheal cannula removed in the past. The other 3 children with postintubation SGS had never had a tracheostomy before. The need for tracheostomy due to worsening stridor was imminent for all of them. Results . The total of seven laryngeal dilatations by balloon esophagoplasty catheter in apneic pause was performed in the 5 children. The procedure averted the need for tracheostomy placement in 4 of them (80%). Failure of dilatation in girl with traumatic stenosis and concomitant severe obstructive lung disease led to repeated tracheostomy. Conclusion . Balloon dilatation of laryngeal stricture could be done in the absence of tracheostomy in apneic pause. Dilatation averted threatening tracheostomy in all except one case. Early complication after the procedure seems to be a negative prognostic factor for the outcome of balloon dilatation.